Exploratory Study Based on Stakeholder Theory in the Development of Accounting Information Systems in the Catholic Church: A Case Study in the Archdiocese of Semarang, Indonesia - Siswanto Fransiscus Asisi Joko; Anggraini Francisca Reni Retno; Widodo Bernardinus Sri (SHS Web of Conferences, 2017)
This study aims to find a strategy in the development of computer-based accounting information system in the church. With exploratory study on the theory of stakeholders, this study identifies the needs of financial information for the purposes of making a decision required by the parish priest, the parish treasurer, and a team of economists at the archdiocese of Semarang (AS). This research was conducted by using qualitative and quantitative approach. Qualitative method is conducted by applying a focus group discussion with economist team in AS (the users who have major influence in the development of the system). In addition to that, quantitative method is also applied to the parish treasurer (the users who have great interest in the system development). The results showed that the parish treasurer has high perceived usefulness, perceived ease of use, perceived of relevance, and the self-efficacy toward the accounting information system (AIS) for the parish. This study provides an answer on the benefits of a bottom-up strategy based on the stakeholder analysis in the development of AIS in the area of the Catholic Church AS.